Application of servqual and servperf methods to assess the quality of teaching services - comparative analysis - Czajkowska, Agnieszka; Manuela, Ingaldi (Manufacturing Technology Journal, 2021)
The features of quality, which is an ambiguous, gradual and very subjective concept, cause that there is no one absolute standard for it. Scientists are looking for ways of its evaluation and improvements of the existing methods. It relates to various areas, but at the same time it is also complex and multi-faceted. There are so many definitions of quality that are constantly evolving. In the paper two meth-ods Servqual and Servperf to assess the quality of teaching services were used. The aim of the paper was to compare the results of the service quality analysis with use of both methods and to indicate the differences between them. It was also checked whether conclusions regarding the quality of ser-vices differ depending on the used research method. The Servqual method takes into account the individual expectations of the respondents, which may affect the assessment of the actual service. It is more complicated, but the results are more adequate to the specifics of the service. It was shown that in one of the areas the results concerning the quality of teaching services differed significantly depending on the used method. However, it is not yet clear which of the two scales is a better meas-ure of service quality.
Keywords: Quality; Service; Servqual; Servperf